SOCIALIZATION PROGRAM OF HEALTH PROTOCOLS FOR EARLY CHILDHOOD - Syarifah Farissi Hamama; Maulida Maulida; Syarifah Fadiya Hallaby (Universitas Muhammadiyah Aceh, 2021)
This social activity was the embodiment of one of the Higher Education Tri Dharma and was carried out by the academic community of the Biology Education Study Program, FKIP Abulyatama University. This activity was held from 01 to 03 June 2021 at Gampong Purada 1 Banda Aceh. The location was chosen because Gampong Peurada is one of the Covid-19 Pandemic Red Zone areas. So it is necessary to conduct socialization related to health protocols, especially for early age children who have high outdoor activities. This activity was carried out to provide an understanding of the application of health protocols in the surrounding environment.Keywords: Covid-19, health protocols, socialization